Effects of temperature and voids on the interfacial fracture of Si/a‐Si3N4 bilayer systems. Issue 9 (12th May 2015) - Lin, Pamela; Babicheva, Rita I.; Xue, Ming; Zhang, Hai Shu; Xu, Huan; Liu, Bo; Zhou, Kun
<x xml:space="preserve">Abstract</x> This work studies the effects of temperature, voids at or near the interface on the interfacial fracture behavior, and mechanisms of the Si/a‐Si3N4 bilayer systems via molecular dynamics simulations. Under mode I loading, at 300 K, the interfacial strength of the bilayer system without voids is ∼22.5 GPa and it undergoes brittle fracture at the interface. However, at 600 K, failure occurs in the a‐Si3N4 layer in a ductile mode. With the existence of void in the Si layer, crack initiates at the void and propagates toward the interface when the temperature is 300 K. However, as temperature increases to 600 K, the defected bilayer system undergoes brittle fracture at the interface at a significantly lowered interfacial strength. With the presence of void at the interface, the bilayer system fractures at the interface with a deteriorated strength regardless of temperature. Under mode II loading, the Si/a‐Si3N4 system undergoes three deformation processes: elastic deformation, followed by plastic deformation in the a‐Si3N4 layer, and subsequently, interfacial sliding. The presence of voids at different locations and the increase in temperature lower the stresses required for interfacial sliding but do not have significant effect on the shear deformation processes. This study provides an insight to fracture behavior of Si/a‐Si3N4 system at certain operating conditions.